Recurrence of Autoimmunity Following Pancreas Transplantation - Burke, George W. (2011)
Pancreas transplantation is a therapeutic option for patients with type 1 diabetes. Advances in immunosuppression have reduced immunological failures, and these are usually categorized as chronic rejection. Yet studies in our cohort of pancreas transplant recipients identified several patients in whom chronic islet autoimmunity led to recurrent diabetes, despite immunosuppression that prevented rejection. Recurrent diabetes in our cohort is as frequent as chronic rejection, and thus is a significant cause of immunological graft failure. Our studies demonstrated islet autoimmunity by the presence of autoantibodies and autoreactive T-cells, which mediated β-cell destruction in a transplantation model. Biopsy of the transplanted pancreas revealed variable degrees of β-cell loss, with or without insulitis, in the absence of pancreas and kidney transplant rejection. Additional research is needed to better understand recurrent disease and to identify new treatment regimens that can suppress autoimmunity, as in our experience this is not effectively inhibited by conventional immunosuppression.